Neonatal hypercalcemia associated with extensive subcutaneous fat necrosis: a case report - Osman, Mahmoud M.; Hamid, Suzan Abdel; Kira, Hussein M.; Alatar, Adel Abdelsalam; Elsabagh, Enas M. (International Journal of Contemporary Pediatrics, 2020)
Subcutaneous fat necrosis (SCFN) of the newborn is rare self-limited fat tissue inflammation that usually occurs in term or post-term newborns exposed to perinatal stress factors, such as perinatal asphyxia, meconium aspiration, neonatal sepsis, and therapeutic hypothermia. SCFN usually appears in the first few weeks of life and has a benign course with spontaneous resolution. Monitoring for complications, in particular the potentially life-threatening hypercalcemia, is crucial. In this report, we describe a male infant with extensive SCFN and neonatal hypercalcemia that went through a prolonged course.